Penerapan Metode SDLC Waterfall Dalam Pembuatan Sistem Informasi Akademik Berbasis Web Studi Kasus Pondok Pesantren Al-Habib Sholeh Kabupaten Kubu Raya, Kalimantan Barat - Yoki firmansyah; Udi Udi (Universitas Merdeka Malang, 2018)
Academic Information System is one of the information that is needed by educational institutions as one As reference for the development and achievement of teaching and learning activities. Academic information systems can also spur teachers to be more transparent in delivering learning outcomes to students and also spur students in improving learning outcomes, so that has more meaning as a communication between teachers and students. This system will also spur all to know the development of boarding school because the existing information system at Al-habib Pondok Pesantren Sholeh Bin Alwi Alhaddad, Currently, Alhabib use the manual system to data processor ex stundents, assessment and processing of academic information. With the existence of this academic information system it will facilitate the admin to provide academic information, facilitate the teacher in providing assessments of students didiknya more easily and transparently, facilitate students and parents learn mngetahui student development. The website also has feature facilitate all obtain information relating to boarding school and will further spur all in using the internet by accessing the academic website of Pesantren Al-habib sholeh Bin Alwi Al-haddad.